Improved performance of AlGaN-based deep ultraviolet light-emitting diode using modulated-taper design for p-AlGaN layer. (5th February 2018) - Lu, L; Ding, G G; Zhang, Y; Liu, Y H; Xu, F J
Abstract: AlGaN-based deep ultraviolet light-emitting diodes adopting modulated-taper design for p-AlGaN layer have been investigated. It is found that remarkable enhancements both in light output power (LOP) and internal quantum efficiency (IQE) can be realized using the modulated-taper design compared to the conventional single-Al-component AlGaN ones. It is verified that the upward energy band of the last quantum barrier, especially symmetric ones, can increase effective potential barrier height for electrons and at the same time, can decrease the barrier height for holes, which is beneficial for high hole concentration distribution within the quantum wells, therefore accounting for the improved IQE as well as LOP.